Changes in germination, early seedling growth and morpho-physiology of sesame under PEG-induced osmotic Stress - Shaik, Khadar Basha; Shaik, Naseem; Vallepu, Suneetha; Mekapogu, Madakka; Patan, Shaik Sha Valli Khan (Current Botany, 2025)
The present study investigates the impact of polyethylene glycol (PEG) (0 and 25%) induced osmotic stress on germination, growth, morpho-physiological responses and stress tolerance indices of thirteen sesame (Sesamum indicum L.) genotypes at an early seedling stage. The experiments were conducted under lab-based controlled cultural conditions with two levels of PEG-6000 (0% and 25%) and thirteen genotypes using diverse seed colours (white, brown, light brown, and black) and twenty-two variables subjected to multivariable analysis. At 25% concentration, the principle component analysis (PCA) biplot classified thirteen sesame genotypes into two groups according to F values. The PCA biplot placed the tolerant (group-I) and sensitive (group-II) genotypes on opposite sides. Group-I contains eight genotypes viz. with black seed colour (IC-132300, GT-10), white seed colour (IC-96229, IC-132171, IC-205471, IC-203962) and light brown seed colours (IC-204966 and IC-131500) Group II contains five sensitive genotypes with brown seed colours such as YLM-17, YLM-66, YLM-11, Madhavi and Gowri, contributed from fresh weight, dry weight, chl a, chl b, total chlorophyll, carotenoids and chlorophyll stability index. The present study offers breeders a laboratory-based, reliable, and quick method for screening sesame germplasm to identify and develop drought-tolerant genotypes contributed from the rate of germination, germination percentage, root length, shoot length, root/shoot ratio, seedling length, dry weight, germination percentage stress tolerance index, root length stress tolerance index, shoot length stress tolerance index, seedling length stress tolerance index, fresh weight stress tolerance index, dry weight stress tolerance index, seedling vigour index and chl a/b.